2017
DOI: 10.7322/jhgd.141277
|View full text |Cite
|
Sign up to set email alerts
|

Night eating syndrome and emotional states in university students

Abstract: Introduction: University students are exposed to many factors related to Night Eating Syndrome (NES), an eating disorder that may be associated with obesity.Objective: To determine the prevalence of NES among students from a Brazilian university and evaluate the association of the syndrome behaviours with emotional, biological and environmental factors. Methods:Cross-sectional study with 200 students from a private higher education institution located in the city of Juazeiro do Norte, Ceará, Brazil. NES was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 38 publications
6
8
3
2
Order By: Relevance
“…Unlike other studies showing a significant relationship among stress, overweight and obesity 5 , 22 , the findings of this study did not show statistically significant differences between weight changes of students, according to the BMI classification and the levels of stress evaluated by the ASNS session (p>0.05). Significant relationships were found with some demographic and health variables.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike other studies showing a significant relationship among stress, overweight and obesity 5 , 22 , the findings of this study did not show statistically significant differences between weight changes of students, according to the BMI classification and the levels of stress evaluated by the ASNS session (p>0.05). Significant relationships were found with some demographic and health variables.…”
Section: Discussioncontrasting
confidence: 99%
“…This behavior may become a habit and people can start using food to relieve stress 1 . Increased consumption of foods in situations of anxiety is frequently reported in the literature 5 , 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the analysis of DASS-21, it was indicated that 43.8% of the Brazilian college students had moderate to extremely severe depression. This result was quite similar to other Brazilian study that used the same measure (Borges et al, 2017), which investigated depression levels in 200 college students from the state of Ceará and identified a proportion of 42.5% of the sample with moderate to extremely severe depression. It is important to highlight that both studies used samples from different Brazilian states, indicating that the university context might generate similar psychological demands regarding depression that may not be dependent on Brazilian regional aspects, or maybe DASS-21 is not influenced by regional variations in its discriminative capacity to assess depression.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the assumption that symptoms of depression, anxiety and stress might overlap (such as negative affect, emotional distress and physiological reactions), a scale that simultaneously assess depression, anxiety and stress in adults was developed, namely the Depression, Anxiety and Stress Scale -DASS-21 (Brown, Chorpita, Korotitsch, & Barlow, 1997). This instrument has recently been adapted and validated to the Brazilian context (Vignola & Tucci, 2014) and it was applied in college students to evaluate their mental health state (Borges, Figueiredo, & Souto, 2017). This instrument has the advantage of assessing three constructs simultaneously, in addition to presenting faster and easier application.…”
Section: Introductionmentioning
confidence: 99%